We Are All in the Same Boat : Cross-Border Spillovers of Climate Risk through International Trade and Supply Chain. (IMF Working Papers; Working Paper ;, 2021)
Are assets in a landlocked country subject to sea-level rise risk? In this paper, we study the cross-border spillovers of physical climate risks through international trade and supply chain linkages. As we base our findings on historical data between 1970 and 2018, we observe that globalization increased the similarity of countries' global climate risk exposures. Exposures to foreign climatic disasters in major trade partner countries (both upstream and downstream) lower the home-country stock market valuation for the aggregate market and for the tradable sectors. We also find that exposures to foreign long-term climate change risks reduce the asset price valuations of the tradable sectors at home. Findings in this paper suggest that climate adaptation efforts in a country can have positive externalities on other countries' macrofinancial performance and stability through international trade.